An Exploration of the Impact of Personality and Role Behaviour on Team Effectiveness - Zhou, Qian (Lily) (Curtin University, 2019)
This study investigates how individual personalities influence team effectiveness. A questionnaire was used to test the relationship between personality and role behaviour as well as how team task specificity and team interdependence moderate the personality-behaviour relationships. Findings of the first, quantitative phase, informed the second, interview phase, which provided additional understanding of the statistical results. Outcomes of this research add to literature by providing new insights into the relationship between personality and team effectiveness.